DCIR suppresses osteoclastic proliferation and resorption by downregulating M-CSF and RANKL signaling - Kaifu, Tomonori; Maruhashi, Takumi; Chung, Soo-Hyun; Shimizu, Kenji; Nakamura, Akira; Iwakura, Yoichiro (Frontiers in Immunology, 2023)
Dendritic cell immunoreceptor (DCIR) is an inhibitory C-type lectin receptor that acts as a negative regulator in the immune system and bone metabolism. We previously revealed that DCIR deficiency enhanced osteoclastogenesis and antigen presentation of dendritic cells, and that asialo-biantennary N-glycan (NA2) functions as a ligand for DCIR. NA2 binding to DCIR suppressed murine and human osteoclastogenesis that occurs in the presence of M-CSF and RANKL. The DCIR-NA2 axis, therefore, plays an important role in regulating osteoclastogenesis in both mice and humans, although the underlying mechanisms remain unclear. Here we found that Dcir−/− bone marrow–derived macrophages (BMMs) exhibited greater proliferative and differentiation responses to M-CSF and RANKL, respectively, than wild-type (WT) BMMs. Moreover, Dcir−/− osteoclasts (OCs) increased resorptive activity and cell fusion more significantly than WT OCs. DCIR deficiency affects gene expression patterns in OCs, and we found that the expression of neuraminidase 4 was increased in Dcir−/− OCs. Furthermore, DCIR-NA2 interaction in WT BMMs, but not Dcir−/− BMMs, decreased Akt phosphorylation in response to M-CSF and RANKL. These data suggest that DCIR regulates osteoclastogenesis by downregulating M-CSF and RANKL signaling, and that DCIR-mediated signaling may contribute to the terminal modification of oligosaccharides by controlling the expression of glycosylation enzymes.